Etnografi Komunikasi Antarpribadi dalam Proses Pemyembuhan Pasien di Rumah Sakit Jiwa Prof. H.B Sa’anin Padang - Efrita, Neni (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Interpersonal communication in the process of recovering from a patient in a mental hospital of Dr. H.B Saanin Padang is very unique, because every different communication activities undertaken in accordance with the communication situation. Interpersonal communication essentially human relationship has entered a stage of psychological conducted between giving health services and inpatient psychiatric mental hospital Dr. H.B Saanin Padang. To see the healing process associated with people who have different psychological retardation. Research methodological approach to be conducted is qualitative constructivist approach to ethnographic analysis of communication. The process of communication between health care providers and patients hospitalized in the healing process in a mental hospital Dr. H.B Saanin Padang in interactive, transactional and dynamic are for the patient who is recovering medically. Form of verbal messages through oral and written speech on bulletin boards, message-shaped form of kinesis and prosaic nonverbal messages, display or factual, and paralinguistic. Ethnography of communication visible component is the genre or type of communication that has different according to the context of the communication, the topic of communication events refers to the type of communication, the communication settings that affect social functioning, communication participant: those involved in communication, verbal and nonverbal forms of messaging, content of the message: explanation and conversation in any type of communication, follow the sequence refers to the form of messages and message content in each event communication and must be done every day, interaction; behavior rules or the action that must be done, interpretation norm; written and unwritten norm that are done by health care providers and hospitalized patients in mental hospital of Dr. H.B Saanin Padang